Newcastle disease virus vector-based SARS-CoV-2 vaccine candidate AVX/COVID-12 activates T cells and is recognized by antibodies from COVID-19 patients and vaccinated individuals - Torres-Flores, Alejandro; Ontiveros-Padilla, Luis Alberto; Madera-Sandoval, Ruth Lizzeth; Tepale-Segura, Araceli; Gajón-Martínez, Julián; Rivera-Hernández, Tania; Ferat-Osorio, Eduardo Antonio; Cérbulo-Vázquez, Arturo; Arriaga-Pizano, Lourdes Andrea; Bonifaz, Laura; Paz-De la Rosa, Georgina; Rojas-Martínez, Oscar; et al. (Frontiers in Immunology, 2024)
Several effective vaccines for severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) have been developed and implemented in the population. However, the current production capacity falls short of meeting global demand. Therefore, it is crucial to further develop novel vaccine platforms that can bridge the distribution gap. AVX/COVID-12 is a vector-based vaccine that utilizes the Newcastle Disease virus (NDV) to present the SARS-CoV-2 spike protein to the immune system. This study aims to analyse the antigenicity of the vaccine candidate by examining antibody binding and T-cell activation in individuals infected with SARS-CoV-2 or variants of concern (VOCs), as well as in healthy volunteers who received coronavirus disease 2019 (COVID-19) vaccinations. Our findings indicate that the vaccine effectively binds antibodies and activates T-cells in individuals who received 2 or 3 doses of BNT162b2 or AZ/ChAdOx-1-S vaccines. Furthermore, the stimulation of T-cells from patients and vaccine recipients with AVX/COVID-12 resulted in their proliferation and secretion of interferon-gamma (IFN-γ) in both CD4+ and CD8+ T-cells. In conclusion, the AVX/COVID-12 vectored vaccine candidate demonstrates the ability to stimulate robust cellular responses and is recognized by antibodies primed by the spike protein present in SARS-CoV-2 viruses that infected patients, as well as in the mRNA BNT162b2 and AZ/ChAdOx-1-S vaccines. These results support the inclusion of the AVX/COVID-12 vaccine as a booster in vaccination programs aimed at addressing COVID-19 caused by SARS-CoV-2 and its VOCs.